2008
DOI: 10.1038/bmt.2008.267
|View full text |Cite
|
Sign up to set email alerts
|

The impact of graft composition on clinical outcomes in unmanipulated HLA-mismatched/haploidentical hematopoietic SCT

Abstract: This study examines the absolute numbers and relative proportions of CD4 þ , CD8 þ , CD14 þ and CD34 þ cells contained in allografts and their impact on early engraftment and later clinical outcomes in 141 patients with hematological malignancies who underwent unmanipulated HLA-mismatched/haploidentical hematopoietic SCT without in vitro T-cell depletion. These patients received G-CSF-primed BM grafts (G-BM) and peripheral blood grafts (G-PB) following a modified regimen of BU/CY 2 plus antithymocyte globulin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…However, in our transplant settings, T-cell dose in the allograft failed to associate with the development of GVHD analyzed by Huang et al 5,32 and in this study. Several possible factors may be responsible for this.…”
Section: Discussionmentioning
confidence: 75%
“…However, in our transplant settings, T-cell dose in the allograft failed to associate with the development of GVHD analyzed by Huang et al 5,32 and in this study. Several possible factors may be responsible for this.…”
Section: Discussionmentioning
confidence: 75%
“…21,44 Other factors, including a lower CD56 dim /CD56 bright NK cell ratio (Ͻ8.0) and a higher CD4/CD8 ratio (Ͼ1.16) in the allografts, may contribute not only to higher risk of acute GVHD but also to increased TRM and decreased OS. 21,42 Recently, Huo et al 45 reported that HLA-B mismatch was an independent risk factor for acute GVHD and TRM after HLA-haploidentical transplantation without ex vivo TCD. Researchers from Japan also showed that among patients with standard-risk diseases who received transplantation from a related donor with an HLA-1 antigen mismatch at the HLA-A, HLA-B, or HLA-DR loci in the graft-versus-host direction, the presence of an HLA-B antigen mismatch was significantly associated with a lower OS rate.…”
Section: Factors Influencing Outcomes Following Unmanipulated Haploidmentioning
confidence: 99%
“…No correlation between FoxP3 + Tregs and aGVHD risk was observed in our centreperformed unmanipulated allogeneic HSCT (without T cell depletion in vitro) [30,31]. Therefore, we sought to clarify whether the different reports of FoxP3 + Tregs in aGVHD were derived from different HSCT methodologies or from differences in Treg subpopulations.…”
Section: Foxp3mentioning
confidence: 99%